INFLUENCERS, HASHTAGS AND CAMPAIGNS: THE ROLE OF INSTAGRAM IN ADVANCING MALE BODY POSITIVITY - Randev, Divya Jyoti (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the role of social media in shaping and advancing the male body positivity movement. The male body positivity movement has recently gained significant traction, challenging traditional masculinity norms and promoting body acceptance among men. Research indicates that men, like women, experience body dissatisfaction, although they often remain silent about it due to societal expectations that frame body image concerns as predominantly a female issue. Social media platforms, especially Instagram, offer men a space to discuss these concerns, share their experiences and build supportive communities. Given that India has the highest number of Instagram users globally, it is important to examine how male body positivity is represented and perceived on Instagram. With a focus on the intersection of digital culture and body image activism, this study examines how online platforms such as Instagram contribute to the dissemination of body-positive messages and the promotion of diverse representations of masculinity in the international and Indian spheres. Utilizing a qualitative approach, the paper analyses user-generated content created by Instagram influencers, body positive movements and hashtags as well as focus group discussions of users from India. This research contributes to a deeper understanding of contemporary discourses surrounding masculinity, body image and digital activism. The study concludes that while social media can reinforce harmful body image ideals, it also has the potential to promote body positivity and self-acceptance.